A strategy perspective on the performance relevance of the CFO - Andreas Venus; Andreas Engelen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Research on functional members of top management teams (TMTs) has increasingly drawn interest to the strategic management field over the past few years. Studies have documented the rise of the chief financial officer (CFO) to pivotal importance and considerable power within the organization. By adopting a contingency perspective and drawing on the coalitional view of the firm, we investigate whether and when a relatively powerful CFO in the TMT is beneficial to firm performance. Multi-source panel data on 292 US firms over the five-year period from 2006 to 2010 revealed that the positive impact of powerful CFOs on performance is strengthened by the degree of unrelated diversification and the firm's tendency toward Defender-type strategies but not by its degree of internationalization.
Keywords: G30; M10; 330; power/resource dependency theory; top management team; finance function; chief financial officer; organizational politics and power; diversification; generic business level strategies; internationalization; panel data analysis; Führungskräfte; Betriebliche Finanzwirtschaft; Macht; Strategisches Management; Unternehmensentwicklung; Schätzung; USA